Local knowledge of homegarden plants in Miao ethnic communities in Laershan region, Xiangxi area, China - Jin Luo; Qiang Li; Jianwu He; Jin Yan; Shujie Zhang; Xuepei Chang; Tao Wu (BMC, 2024)
Abstract Background Homegardens are small-scale land use systems with significant implications for local livelihoods, biodiversity conservation, and sustainable development due to their diverse flora and fauna. Conducting homegarden surveys enables researchers to gain insights into the traditional ecological knowledge of indigenous communities, preserve homegarden biodiversity, and promote sustainable livelihoods. This study has two objectives: first, to collect, record, and organize data on homegarden plants and related traditional knowledge from three communities in the Laershan Plateau, and second, to analyze the species and functional diversity of homegarden plants in the region while exploring the factors that contribute to the heterogeneous distribution of these plants among the communities of three townships. Methods This research employed field surveys in the Laershan Miao Autonomous Region in Xiangxi, China, from September 2021 to August 2023. Data were collected through observation and semi-structured interviews. The study utilized descriptive statistics and quantitative analysis, including the Relative Importance Value (RI), Use Value Index (UV), Jaccard Index (JI), and Comprehensive Index of Land Use Degree (La), to examine the diversity of local homegarden plants and related traditional knowledge, as well as community heterogeneity. Results The study area exhibited rich biodiversity, with 152 plant species recorded belonging to 62 families and 124 genera. These findings highlight the importance of homegarden plants in maintaining ecological balance and enhancing system resilience against disturbances. Homegarden plants serve multiple functions such as food, ornamental, medicinal, and fodder purposes, with edible and trade plants having the most abundant knowledge. Furthermore, this research revealed that communities with similar forest resource compositions may have similar homegarden plant compositions, demonstrating the connection between cultural exchange among different communities and patterns of plant species distribution. Conclusions The Laershan region boasts diverse homegarden plant species crucial for ecological balance and resilience. Their multifunctionality reflects human impact. Plant diversity varies with residents' lifestyles, needs, and cultural exchanges. The close connection between plants and local life is clear. Factors like resource distribution, cultural exchange, and lifestyle influence plant distribution. Further research is needed for conservation and sustainable development. Future research should focus on culturally valuable plant species and traditional knowledge applications.